PENGARUH ORIENTASI WIRAUSAHA TERHADAP KINERJA PERUSAHAAN KECIL DENGAN LINGKUNGAN DAN STRATEGI SEBAGAI VARIABEL MODERAT (STUDI KASUS PADA INDUSTRI ANEKA DI KOTA SEMARANG) - Nasir, Mohamad; Handoyo, Agus (JURNAL BISNIS STRATEGI, 2003)
Studies examining the effect of entrepreneurial orientation on firm performance,in which environment and strategy act as moderating variable. The main focus of the study is an approach using contingency theory. The theory states an assessment on how to overlook the effect of fit or match interactions between entrepreneurial orientation as independent variable and environment and strategy as moderating variables influence firm performance as dependent variable. Object of the study is multiple small industry available in Semarang with the respondents are the management of the industries. Data available was gained from distributed questioner directly to the respondents according to the multiple small industries listed in Kantor Dinas Perindustrian dan Perdagangan Semarang Municipality. Entrepreneurial orientation is conceptualized into dimensions such as innovativeness, proactiveness, and risk taking. Environmental variables are derived from heterogeneity, dynamism and unpredictability. Strategy as moderating variable consists of such dimensions as variable marketing differentiation, innovative differentiation, and cost leadership. Moderating regression analysis was used for examining the direction of interaction relationship. Findings from the study shows that both environment and strategy moderate the relatioship entrepreneur orientation to firm performance. Partial derivative approach illustrates a positive relationship available between the characteristic of moderations. Thus, the higher the value of moderate variables, the higher the effect of independent variables towards the performance of the firm. Unlike the proposed hypotheses, this study explains that cost leadership strategy as moderate variable indeed positively moderated towards the relationship between entrepreneurial orientation and firm performance.